A Project Based Approach to Teach Object Oriented Modeling and Design Patterns - Margaret, R. E.; Vinod, A. M.; Tejonidhi, M. R. (Journal of Engineering Education Transformations, 2025)
Object oriented techniques incorporate different software engineering techniques that can be used in development of all projects. Unified Modeling Language (UML) is a structured method which involves formal methodologies, and has made significant contribution in defining set of methodologies that can be applied to any software engineering effort. Our approach is to make students experience the real time application of Object Oriented Modeling and Design methods using supportive tools that help them to have a hands-on experience with the operational software design. This helps students to use emerging object oriented techniques to improve their knowledge on object oriented modeling and design, problem solving skills and team work skills that can be converted into useful computer applications.